PERAN STAKEHOLDERS DALAM KONSERVASI SUMBER DAYA AIR DI WADUK JATIBARANG KOTA SEMARANG - Yumna Salsabila, Fadhila; Purnaweni, Hartuti; Rina Herawati, Augustin (Journal of Public Policy and Management Review, 2024)
The conservation of water resources at the Jatibarang Reservoir in Semarang City is crucial for maintaining and ensuring the availability of water needed to support the well-being of the community in Semarang City. This is due to the high demand for water resulting from the increasing population, while the Water Quality Index of Semarang City is experiencing a decline. This issue is not only felt by a single sector, making the role of stakeholders important. This research aims to identify the stakeholders involved and understand the roles of each stakeholder in the conservation of water resources at the Jatibarang Reservoir in Semarang City. The method used in this research is descriptive qualitative, with data collection techniques through in-depth interviews, observation, and document study. This research uses Bryson's stakeholder mapping theory to identify the stakeholders involved and Nugroho's theory to understand the roles of each stakeholder. The results of the research show that the stakeholders fall into the following categories: (1) Players, which include BBWS Pemali-Juana, acting as policy creator, implementer, coordinator, and facilitator; the Environmental Agency of Semarang City, the Fisheries Agency of Semarang City, and the Sukomakmur Tourism Awareness Group, acting as policy creators, implementers, and facilitators; (2) Subjects, which include the Gunungpati Subdistrict, Kandri Village, and the community, acting as implementers; (3) Context Setters, which include the Tourism Agency of Semarang City, acting as accelerators; and (4) Crowd, which includes educational institutions and environmental community groups, acting as accelerators. The recommendations provided include rebuilding coordination through the provision of training and development, resource allocation, implementation of adaptable policies and cross- sectoral institutional synergy with the authorities through community education, assistance or monitoring, and reporting.